Harmonising Family Law - Atkin, Bill (Victoria University of Wellington Law Review, 2006)
On 25 July 2006, Bill Atkin delivered his inaugural lecture after becoming a professor in the Law Faculty of Victoria University of Wellington. He took as his theme the state of disharmony in family law. While historically the focus of the law was narrow and consistent, a series of reforms has meant that family law’s brief has widened and become something of a jumble. This is true of the law relating to adults as well as that relating to children. While there is plenty of scope to undertake a project to bring greater harmony to family law, the task may be forlorn. There are many forces militating against rationalisation of the law, ranging from diversity of family types and clashing ideologies to the realities of politics.